Osteotome-Induced Blood Clot and Subsequent Bone Formation with the Use of Collagen Sponge for Integration of Single Dental Implants into the Atrophied Posterior Maxilla: A Retrospective Follow-Up of 36 Implants after 5 to 13 years - Stefano Volpe; Michele Di Girolamo; Paolo Pagliani; Sandro Zicari; Lars Sennerby (International Journal of Dentistry)
Background. Atrophy of the posterior maxilla as a consequence of tooth loss and sinus pneumatization is a frequent condition encountered in the clinical practice. Prosthetic rehabilitation with implants in these patients often requires some kind of bone regeneration procedure to increase the bone volume. Aim. The aim of the present retrospective study is to analyze the survival and success rates of a series of implants placed in the atrophic posterior maxilla with a transcrestal osteotome procedure, without placing a bone grafting material. Materials and Methods. From 2006 to 2014, 36 dental implants (Neoss Ltd., Harrogate, UK) were inserted in 36 patients with at least 4 mm of bone below the maxillary sinus using transcrestal osteotome sinus floor elevation and placement of collagen sponge below the sinus membrane. ISQ measurements were made after implant placement and at abutment surgery after 4 to 6 months. The vertical bone height (VBH) was evaluated in intraoral radiographs taken prior to surgery and in radiographs from annual check-up appointments 5 to 13 years after implant placement. In addition, marginal bone loss (MBL) was evaluated. Results. One implant was lost after four years of prosthetic loading. The remaining 35 implants showed no complications and were loaded with single crowns after 4–6 months of healing. All 35 implants showed clinical success after 8.5 ± 2.8 years of prosthetic loading (from 5 to 13 years). The vertical bone height was 5.9 ± 1.4 mm at surgery, 9.7 ± 1.1 mm at second surgery after 4–6 months, and 8.3 ± 1.8 at the follow-up at 8.5 ± 2.8 years (from 5 to 13 years). The implant stability registered was 73.2 ± 6.2 ISQ at the surgery and 75.8 ± 3.9 at the second surgery after 4–6 months. Conclusions. The present long-term follow-up study showed that the crestal approach for sinus floor bone augmentation without additional bone grafting results in predicable bone formation and high implant survival. The osteotome technique is a valid alternative to the more invasive lateral window technique in single cases with a minimum of 4 mm of VBH below the maxillary sinus.